Toward global maps of internal tide energy sinks. (May 2019) - de Lavergne, C.; Falahat, S.; Madec, G.; Roquet, F.; Nycander, J.; Vic, C.
Abstract: Internal tides power much of the observed small-scale turbulence in the ocean interior. To represent mixing induced by this turbulence in ocean climate models, the cascade of internal tide energy to dissipation scales must be understood and mapped. Here, we present a framework for estimating the geography of internal tide energy sinks. The mapping relies on the following ingredients: (i) a global observational climatology of stratification; (ii) maps of the generation of M2, S2 and K1 internal tides decomposed into vertical normal modes; (iii) simplified representations of the dissipation of low-mode internal tides due to wave-wave interactions, scattering by small-scale topography, interaction with critical slopes and shoaling; (iv) Lagrangian tracking of low-mode energy beams through observed stratification, including refraction and reflection. We thus obtain a global map of the column-integrated energy dissipation for each of the four considered dissipative processes, each of the three tidal constituents and each of the first five modes. Modes ≥6 are inferred to dissipate within the local water column at the employed half-degree horizontal resolution. Combining all processes, modes and constituents, we construct a map of the total internal tide energy dissipation, which compares well with observational inferences of internal wave energy dissipation. This result suggests that tides largely shape observed spatial contrasts of dissipation, and that the framework has potential in improving understanding and modelling of ocean mixing. However, sensitivity to poorly constrained parameters and simplifying assumptions entering the parameterized energy sinks calls for additional investigation. The attenuation of low-mode internal tides by wave-wave interactions needs particular attention. Highlights: A framework for estimating the global geography of internal tide energy sinks is presented. The column-integrated dissipation rate of internal tides is mapped globally. The estimated internal tide dissipation compares well with finestructure observations. The maps pave the way toward comprehensive 3D mapping and parameterization of tidal mixing.